2012
DOI: 10.1108/08876041211199689
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of consumer attitude toward service innovation – the evidence of ETC system in Taiwan

Abstract: Purpose -Innovation has attracted considerable interest in recent years in improving competitive advantage for both profit and nonprofit organizations. Service innovation offers the potential for substantially improving the performance, but performance gains are often obstructed by users' unwillingness to accept and use available systems. This research aims to use the concept of Reasoned Action Theory to further examine consumer attitudes toward service innovation and its antecedents. Design/methodology/approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 45 publications
2
56
1
1
Order By: Relevance
“…There appears to be a lack of studies using attitude as a mediating variable between predictors (brand architecture, CSR, internet marketing, trust, perceived value) and corporate image in past studies. The common direct predictors of attitude investigated in previous academic research are brand architecture [17], [27], [28], trust [14], [15], [19], [20], CSR [21], perceived value [15], [30], [31], internet marketing [20], [21], [29]. Their direct relationships with consumer attitude are equivocal or mixed.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There appears to be a lack of studies using attitude as a mediating variable between predictors (brand architecture, CSR, internet marketing, trust, perceived value) and corporate image in past studies. The common direct predictors of attitude investigated in previous academic research are brand architecture [17], [27], [28], trust [14], [15], [19], [20], CSR [21], perceived value [15], [30], [31], internet marketing [20], [21], [29]. Their direct relationships with consumer attitude are equivocal or mixed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature has shown that there are many factors that affect consumer attitudes, such as brand architecture [17], [27], [28], internet marketing [29], CSR [14], trust [14]- [16], [19], and perceived value [15], [30], [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study replicate a model of the consumer's intention to use service innovation which was developed by Lee (2012). In the specific, the model is applied to examine people intention to use E-toll card system as a service innovation.…”
Section: Introductıonmentioning
confidence: 99%
“…The fact has shown that there were only 5.88% of all the total transactions in the toll gates which has E-toll card fasility (Jasamarga, 2010, p. 20). Therefore, this study aimed to identify the antecedents factors that influence consumer attitude toward service innovation (Lee, 2012).…”
Section: Introductıonmentioning
confidence: 99%
See 1 more Smart Citation